Sacrifice and Satisfaction: Exploring The Quality of Life of Public Secondary School Volunteer Teachers in Remote Areas - Leon, Maricris Bullon; Mokamad, Romar F.; Almirante, Jean F.; Mandado, Aneve Y.; Barcenal, ShaMyca E.; Salvadico, John Lloyd; Salendab , Rysa Lee Ann Ocariza; Salendab, Fahad (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study explored the quality of life of selected secondary school volunteer teachers in the remote areas of the Schools Division of Sultan Kudarat. This qualitative study utilizes phenomenology as its method and used convenience sampling as the sampling technique. Six (6) volunteer teachers were the study's participants. Moreover, the study employed a semi-structured interview guide with open-ended questions, and the data were analyzed using Thematic Analysis. Through thematic analysis, some emerging themes were extracted after an exhaustive and systematic process of thematic coding, analysis, and categorizations of the transcripts from the interview. Such themes include teachers' passion for teaching, enhancement of teachers' skills, teachers' psychological condition, qualifications, financial stability, long-distance travel, unsafe roadways, classroom management skills, faith, community linkages, classroom management skills, seminars and training, multi-talented teachers, and allowances. This study concludes that volunteer teachers in remote areas need more financial stability. Some of the teachers have limited seminars and training attended. Although they show incredible resilience and courage, they cannot cope with the increasing daily expenses, and a positive outlook cannot buy even the necessities a teacher needs to sustain himself, their family, and even the teaching-learning process itself. The study recommends that more be done to support and train volunteer teachers. Initiatives like professional development programs, access to teaching resources, provision of allowances and hazard pay, provision of plantilla positions in remote areas, and social support networks can go a long way in supporting volunteer teachers and improving education in remote areas.